Family member death among formerly incarcerated persons. Issue 2 (7th February 2021) - Testa, Alexander; Jackson, Dylan B.
Abstract: Bereavement carries consequences for the health and socioeconomic well-being of surviving family members. Using data from the National Longitudinal Study of Adolescent to Adult Health, the current study investigates whether formerly incarcerated individuals experience the death of a family member at higher rates than the general population. We find that relative to those without a history of incarceration, formerly incarcerated individuals are more likely to experience the death of an immediate family member by young adulthood. Subsequent analyses demonstrate that deaths occurring during or after a respondent was incarcerated were relevant for health and well-being.